ANALISIS MANAJEMEN RISIKO PRODUK KAFALAH (STUDI PADA BANK MUAMALAT INDONESIA BANDA ACEH) - Satria Munawir (Share: Jurnal Ekonomi dan Keuangan Islam, 2014)
Kafalah is a guarantee of a guarantor, either in the form of self assurance and treasure to the second party in relation to the rights and obligations of both parties that the other party. In banking sector, implementation of the concept is well known as a bank guarantee, which is a guarantee in the form of paper issued by the bank which resulted in the obligation to pay to the party receiving the collateral if the guaranteed party breach the contract. This article aims to study the implementaion of kafalah product at BMI Banda Aceh including strategies in preventing risks related the products. It also examines the implementation of kafalah from an Islamic perspective. In finding the answer, this article employes qualitative approach. Data was collected through field research and library research which was then analized using descriptive analysis method. The results show that the product kafalah undertaken by BMI Branch of Banda Aceh is a form of insurance that includes guaranteed tender, performance bonds, warranties advance, and guarantee maintenance with a deposit of 100% cash collateral to the insurance value is small and a deposit of 60% of fixed asset plus 40% cash collateral for eprtanggungan whose value is greater than the value of the desired assurance customers. Moreover, the client or the insured must enter into cooperation agreements with project leaders to work on a particular project. Tips management undertaken by BMI Branch Banda is analyzing the customer or contractor using character analysis and collateral is more dominant than the overall analysis of 5C, because the BMI-related risks faced by the provision of guarantees / kafalah is credit risk and reputation risk. From the Islamic perspective, the implementation of kafalah has complied with Islamic jurisprudence. Keywords: Analysis, Risk Management, Kafalah, Bank Muamalat Indonesia